Pengaruh Layanan Go-Food, layanan Go-Send dan Bonus Insentif terhadap Pendapatan Driver Go-Jek Di Kota Padang Pasca Pandemi - Melisa Sundari Putri Melisa; Desi Handayani; Randy Heriyanto (Politeknik Negeri Padang, 2022)
This study aims to determine whether Go-Food services, Go-Send services, and incentive bonuses have an effect on Go-Jek driver income after the Pandemic. This data of research is quantitative research. The data collection method in this study used a questionnaire. The population of this study are all Go-Jek drivers in the city of Padang. The sample used in this study were Go-Jek drivers in the city of Padang who had met the criteria of reaching 97 people. The data analysis of this study used multiple linear regression analysis using the SPSS version 25 program. The results of this study indicate that Go-Food services, Go-Send services, and incentive bonuses have a positive and significant effect on the income of Go-Jek drivers in Padang City. Keywords: Go-Food Service, Go-send Service, Incentive Bonus and driver income